2008
DOI: 10.1152/ajpregu.00035.2008
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ghrelin treatment stabilizes body weights of senescent male Brown Norway rats at baseline and after surgery

Abstract: Yukawa M, Weigle DS, Davis CD, Marck BT, Wolden-Hanson T. Peripheral ghrelin treatment stabilizes body weights of senescent male Brown Norway rats at baseline and after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
(109 reference statements)
2
9
0
Order By: Relevance
“…In the present experiments, ipamorelin treatment of rats with POI improved body weight gain after surgery. Our finding is in agreement with the results of a recent study showing that postoperative ghrelin treatment decreased the production of proinflammatory cytokine interleukin-6 and stabilized the body weight in senescent rats after surgery (Yukawa et al, 2008). However, additional studies specifically designed to investigate the effect of ipamorelin on inflammatory cytokine production are required to confirm its anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 93%
“…In the present experiments, ipamorelin treatment of rats with POI improved body weight gain after surgery. Our finding is in agreement with the results of a recent study showing that postoperative ghrelin treatment decreased the production of proinflammatory cytokine interleukin-6 and stabilized the body weight in senescent rats after surgery (Yukawa et al, 2008). However, additional studies specifically designed to investigate the effect of ipamorelin on inflammatory cytokine production are required to confirm its anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we show for the first time that the effect of ghrelin on body weight is agedependent, being most pronounced in the youngest rats. Importantly, although less prominent, the response of older rats to a stimulatory effect of ghrelin on body weight was still significant, which agrees with the ability of peripheral ghrelin to prevent body weight loss in senescent Brown Norway rats (Yukawa et al, 2008). Also, i.c.v.…”
Section: Discussionsupporting
confidence: 76%
“…The finding of increased adiposity without increased FI supports findings of a previous study indicating that central ghrelin can alter adipocyte metabolism independently of an effect on FI. Other studies have shown that ghrelin stimulates adipogenesis [19], alters energy partitioning into fat [20], and decreases sympathetic activity and metabolic rate [21], also supporting a FI-independent effect of ghrelin on adipose tissue metabolism. In our study, the lack of effect on FI was likely due to the much lower doses that we tested, compared to other studies showing both increased adiposity and increased FI with ICV or peripheral ghrelin treatment (see, for example, [14,22]).…”
Section: Discussionmentioning
confidence: 77%